Influence of Different Essential Oils on Refrigerated Fish Patties Produced from Bonito Fish (Sarda sarda Bloch, 1793) - Guran, Husnu Sahan; Oksuztepe, Gulsum; Coban, Ozlem Emir; Incili, Gokhan Kursad (Czech Academy Agricultural Sciences, 2015)
The effects of different concentrations of thyme (group T), dove (group Cl), and rosemary (group R) extracts on the microbiological, chemical, and sensory attributes of fish patty made from the bonito fish (Sarda sarda Bloch, 1793) were investigated. The numbers of total mesophilic aerobic bacteria, coliform bacteria, Staphylococcus Micrococcus spp. and yeasts and moulds in group R were lower than those of the other groups during storage (P < 0.05). During the storage period, total volatile basic nitrogen (TVB-N), thiobarbituric acid index (TBA-i), peroxide values, and free fatty acid content gradually increased in all groups, and significant differences were found between the groups (P < 0.05). The results of sensory evaluation showed that the shelf life of fish patties was 4 days for the control group, and 8, 10, and 14 days for the groups treated with thyme, clove and rosemary essential oil, respectively (P < 0.05). In conclusion, the addition of essential oils showed a positive effect on the product shelf-life; and in particular, rosemary essential oil produced a remarkable effect.
Keywords: bonito fish; thyme oil; clove oil; rosemary oil; shelf-life